Do planejamento à prática: a influência de um material didático na prática de um grupo de professores em formação em Química - Daniela Martins Buccini (2016)
Curriculum guidelines, under discussion in Brazil, have emphasized the importance of social and cultural formation of citizens. In this sense the research in education have argued around a more innovative teaching, in which to overcome the model of transmission of information and pre-established concepts. In this model are disregarded preconceptions of students, the way they learn, the need for interaction between teacher and student and between the students themselves and all the content. Some educational trends have been widely discussed in the literature. Among such trends some guidelines arising from the STS movement, Science-Technology-Society and the importance of encouraging students to expose their opinions and engage in class discussions. The use of these contemporary trends in education exposes the importance of the teacher's role as mediator of these processes and as a promoter of this kind of discussion. It is indicated that the initial training courses for teachers prepare for that in a process of reflection, these professionals understand the importance of developing more contextualized classes that make the student protagonist of their own learning. Considering the need for a greater understanding of the training of teachers, this study analyzed the use of a specific teaching material, written with the intention to facilitate the appropriation by the teacher to the contemporary trends of education. From this, this study followed the lessons of Chemistry student teachers who participated in the project motivating Practice of Chemistry in the Public Schools of Minas Gerais. Data collection occurred in two ways: observation and filming of classes and meetings. Group meetings and all classes in which student teachers used the teaching material were recorded. We started the analysis by meetings focusing at this stage: presentation of the material and first contact, first impressions on the use of the material and some discussions that emerged from the analysis that undergraduates have made of this material. From the results obtained through the meetings, we start to analyze the lessons. The analytical focus of this stage were using (or not) of the material by licensees and how they used it. From the understanding of how occurred the use of the material, we started to analyze the interaction of teachers in terms of Communicative Approach (Mortimer and Scott, 2002 and 2011) and as the discourse of teachers in training may have been influenced by the use of the material. In general, we realized that most undergraduates use the material in any way and that their use has raised some important discussions and conflicts that made these licensees reflect on their practice and the way they handled a didactic material. We realize the analysis of lessons that teachers in training, in general, were very interactive, as the dialogical speech was rarer. Despite not having acquired full ability on some trends, student teachers had the opportunity of experiencing different teaching practices of traditional and reflect on them. Even for those who do not fully appropriated contemporary trends in education, we believe that this experience and the conflicts arising from it are already important and are configured in a formative process.